A revised classification of the genus Matrona Selys, 1853 using molecular and morphological methods (Odonata: Calopterygidae). (23rd June 2015) - Yu, Xin; Xue, Junli; Hämäläinen, Matti; Liu, Yang; Bu, Wenjun
<x xml:space="preserve">Abstract</x> An extensive review of the genus Matrona is presented based on mitochondrial (COI) and nuclear (ITS) sequences from 150 samples which cover all the known taxa of this genus. The separation of two main clades (oreades group: M. oreades, M. corephaea and M. taoi; basilaris group: M. basilaris, M. nigripectus, M. cyanoptera, M. japonica and M. annina) is strongly supported. The classification of all traditional recognized species is confirmed. The Hainan population separates very well from mainland M. basilaris populations, which is also confirmed by geometric morphometric analysis of wing shape. Given the implications of the molecular analysis the genus Matrona is grouped into two subgenera: subgen. Matrona (type species M. basilaris) and Divortia subgen. nov. (type species M. oreades). A new species, M. (M.) mazu sp. nov., from Hainan is described. Brief taxonomic notes on the nine recognized species of the genus are given. Lectotype designations of M. basilaris and M. nigripectus are published. © 2015 The Linnean Society of London